Brachiosaurus the nosy dinosaur - Veitch, Catherine; Forshaw, Louise (Essex, England Miles kelly, 2019)
Bobby the Brachiosaurus is always using his long neck to stick his nose into other dinosaurs' business. It's not long before Bobby gets himself into trouble, but will anyone come to help him?
English stories
2
Keywords: Dinosaurs -- Juvenile fiction; English stories